PENINGKATAN MUTU PENDIDIKAN AGAMA ISLAM MELALUI KAJIAN RUTIN KEAGAMAAN MAHASISWA - Siti Nursyamsiyah (Universitas Muhammadiyah Jember, 2018)
Ability to manage and develop tertiary educational institution is important. TAbility to manage and develop tertiary educational institution is important. This may be done in line with the principles of modern management oriented to the quality. For the owners and managers of universities, the quality management system is essentially nucleated on continuous improvements to strengthen and develop the quality of graduates that can be absorbed by the agency and the labour market. As we know that the globalization era is the era of competition the quality or the quality of a product quality will be in demand by consumers, otherwise if the product is not quality it will be abandoned by consumers. Likewise College in the era of globalization must be based on quality, how the College in the activities of educational services and the development of human resources has advantages. Given the MEA era, is a challenge for students, especially in religious and moral behaviour. So with the regular review is to strengthen religious faith Muhammadiyah university of Jember students of education Islamic religion. keywords: quality of education, the study of religious routines